(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Leadership in higher education plays a crucial role in shaping academic institutions and influencing their growth. Effective leadership is driven by a combination of personal traits, sociocultural influences, and psychological development. This article explores the key characteristics of leadership among higher education leaders and examines the socio-psychological factors that contribute to their development. It highlights the significance of vision, adaptability, ethical leadership, and emotional intelligence in educational leadership. Furthermore, it discusses how socialization, cultural background, and psychological resilience impact leadership styles and decision-making in academic institutions